Maiyahan as a Model of Cak Nun’s Transformative Islamic Education - Ma'arif Jamuin; Yulia Eka Saputri (Iseedu: Journal of Islamic Educational Thoughts and Practices, 2017)
Emha Ainun Najib, best known as Cak Nun, is a prominent writer, humanist, “dai” or “ulama”, and a preacher. Despite his profound concerns on social, political, cultural and religious issues, he expresses them in simple language and accordingly, is explicable to the lower-class society. He named it “Maiyah”, or “Maiyahan” as a forum to articulate and convey his views. It is a medium to critically discuss various social, cultural, political, or religious issues. As a medium of da'wah (tabligh), it can be classified as non-formal education based on educational perspective. Supported by his populist style, and exceptional literary and rhetorical ability, he evokes the critical reason of his congregation and promotes a sociable and understandable tabligh. In contrast to the design of formal education, non-formal education has no time-constraint and the materials are miscellaneous. Unlike general tabligh, which is commonly a one-way communication and normative, Maiyah discusses actual issues in dialogic forum. It is closer to critical education model which aims to construct participants’ critical awareness towards a transformation of social structure.